A Fresh Look at 'Relational' Values in Nature: Distinctions Derived from the Debate on Meaningfulness in Life. (1st August 2020) - Neuteleers, Stijn
Abstract : Some recent policy-oriented publications have put forward a third category of environmental values, namely relational or eudaimonic values, in addition to intrinsic and instrumental values. In this debate, there is, however, much confusion about the content of such values. This paper looks at a fundamental debate in ethics about a third category of reasons besides reasons from morality and self-interest, labelled as reasons of love, care or meaningfulness. This category allows us, first, to see the relation between relational and eudaimonic values, and, second, to make clear and applicable distinctions between the relational valuing of nature and moral or instrumental valuing.